ANALISIS BIAYA-VOLUME-LABA SEBAGAI ALAT PERENCANAAN LABA PADA PABRIK TAHU PINK JAYA – OEBUFU, KUPANG - Karolus Belmo; Marianus Saldanha Neno (Universitas Nusa Cendana, 2020)
Cost-volume-profit analysis is often simply described as a break even analysis. However, companiesshould also be aware that break even analysis is a key of cost-volume-profit analysis. Researchers chosePabrik Tahu Pink Jaya in Oebufu Kupang as the research location. Researchers got information aboutproblems in location was the production process. The owner doesn't count all the costs of production insetting the cost of goods sold so that profit could not reach target. The objectives of the research are (a)to find out how many units should be sold at the break even point level; (b) to find out how manyrupiahs are at the break even point level; and (c) to find out how many units must be sold to reach theprofit target. Based on the results of research, conclusions consist of (a) the number of units sold out atthe break even point level is 21,185 boards; (b) the amount of rupiah at the break even point level is Rp.794,448,433, -; and (c) the number of units sold out to achieve the profit target were 17,980 boards withsales of Rp. 674,250,000, - Keywords: Cost-Volume-Profit Analysis, and Profit Planning